Academically meaningful play: Designing digital games for the classroom to support meaningful gameplay, meaningful learning, and meaningful access. (March 2023) - Clark, Douglas B.; Hernández-Zavaleta, Jesús E.; Becker, Sandra
Abstract: What does it mean for a game to engage players in academically meaningful play? Much has been written about the integration of educational learning within the design of games in terms of intrinsic/endogenous design. While these framings capture the positioning of learning within games, they provide less insight into what might distinguish design choices that are powerful in terms of both learning and gameplay from design choices that might be limiting from one or both of these perspectives. In this article, we therefore propose a framework for thinking about academically meaningful play that builds upon and extends more general ideas about meaningful play (Salen & Zimmerman, 2003). The proposed framework focuses on (a) discernability of choice outcomes, (b) integration of choice outcomes into unfolding game state, (c) meaningful choices grounded in core academic ideas, and (d) thematic and challenge access. We analyze three academic games that focus on geometric transformations as comparative cases to consider the potential affordances of the proposed framework for analyzing the implications of design choices. Highlights: Intrinsic framings of game design focus only on location of learning mechanics. Intrinsic design, endogenous design, and disciplinary integration are examples. Academically meaningful play articulated as a framework for educational game design. Academically meaningful play extends ideas about meaningful play from game design. Comparisons across three cases highlight contributions beyond intrinsic design.